The role of BDNF as a mediator of neurobiological and clinical improvements in Parkinson’s disease patients following HIIT: A comprehensive review. - Gańska, Oliwia Zuzanna; Sochocka, Agata; Janik, Dominika; Nowicka, Nina; Szepietowska, Martyna; Zapart, Zuzanna; Bundyra, Jakub; Mian, Emil; Sikorska, Alicja; Parda, Julia (Quality in Sport, 2026)
Background. Parkinson’s disease (PD) is characterized by progressive dopaminergic neurodegeneration and significantly reduced levels of Brain-Derived Neurotrophic Factor (BDNF). High-Intensity Interval Training (HIIT) has emerged as a critical non-pharmacological strategy to stimulate neuroplasticity via the muscle-brain axis. Aim. This review evaluates the role of BDNF as the primary biological mediator of the neurobiological and clinical improvements observed in PD patients following HIIT interventions. Material and methods. A structured analysis was performed on 28 scientific publications (2008–2026) sourced from PubMed. The methodology synthesized molecular signaling pathways with standardized clinical outcome measures. Results. HIIT-induced elevations in blood lactate and irisin trigger the PGC-1α/BDNF pathway, crossing the blood-brain barrier to enhance mitochondrial quality control and neuronal survival. Clinical evidence demonstrates a 21.6% mean reduction in MDS-UPDRS Part III scores, alongside significant improvements in gait economy, executive functions, and respiratory mechanics. HIIT further mitigates depressive symptoms through BDNF-modulated neurotransmission. Conclusions. BDNF is the central driver of the multi-systemic benefits associated with HIIT. Providing a more robust neurotrophic stimulus than moderate-intensity exercise, HIIT acts as a potent disease-modifying therapy. Early implementation of individualized HIIT protocols is essential for optimizing long-term psychomotor resilience.